2004
DOI: 10.1093/rheumatology/keh397
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Italian patients with systemic lupus erythematosus. I. Relationship between physical and mental dimension and impact of age

Abstract: Both PCS and MCS contribute to the decrease in HRQOL in SLE patients. In SLE the mutual interaction between these two dimensions seems to be more relevant than in healthy people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 14 publications
11
52
0
4
Order By: Relevance
“…Similarly, Rinaldi et al, 19 when examining the QOL of Italian women in a cohort of 126 patients with the disease and 96 healthy controls, found that mental and physical components were reduced only in patients with active disease.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Rinaldi et al, 19 when examining the QOL of Italian women in a cohort of 126 patients with the disease and 96 healthy controls, found that mental and physical components were reduced only in patients with active disease.…”
Section: Discussionmentioning
confidence: 82%
“…17 Other studies show similarity to the results of this research with respect to mean age at the time of diagnosis. 2,16,[18][19][20]24 The diagnosis of SLE is always a nuisance, 21 leaving young women anxious because it occurs in a productive and crucial phase of their life, a time to stabilize their relationships, constitute a family, or choose a career. The author's argument quoted previously is consistent with the results of this study, as the SLE patients were on average 34 years old, but at the time of SLE diagnosis they were on average six years younger.…”
Section: Discussionmentioning
confidence: 99%
“…Mientras por el contrario, otros estudios han hallado una CVRS más desfavorable en pacientes con LES en comparación con muestras de control sanas y aún más con otras enfermedades crónicas (Abu-Shakra, et. al., 1999;Alarcón, et al, 2004;Jolly, 2005;Kulczycka, et al, 2008;Lash, 1998;Meenakshi, 2005;Rinaldi, et al, 2001;Rinaldi, et al, 2004).…”
Section: Discussionunclassified
“…The importance of assessing HRQL in patients with chronic pain has been documented by our recent studies of patients with inflammatory rheumatic diseases (RA, psoriatic arthritis and ankylosing spondylitis) (70), systemic lupus erythematosus (81,82), symptomatic knee and hip osteoarthritis (69), postmenopausal women with vertebral fractures (83), and fibromyalgia (59). In comparison with healthy controls, all of the rheumatic conditions significantly impaired all eight health concepts of the SF-36 in both the physical and mental component, but the disease with the worst HRQL for these dimensions was RA (70).…”
Section: Health-related Quality Of Life Assessmentmentioning
confidence: 99%
“…In comparison with healthy controls, all of the rheumatic conditions significantly impaired all eight health concepts of the SF-36 in both the physical and mental component, but the disease with the worst HRQL for these dimensions was RA (70). Overall, the dimensions typically affected in inflammatory rheumatic diseases were physical functioning, limitations due to physical function, and bodily pain, whereas the level of perceived HRQL in patients with fibromyalgia seems to be explained more by their mental health than by their physical condition (59,69,70,(81)(82)(83). A number of pain-related quality of life selfadministered instruments have been constructed to evaluate pain-related functional disturbances in specific diseases or pain conditions in which the patient is asked to list the activities or tasks they regularly performed before the onset of pain but have since found difficult.…”
Section: Health-related Quality Of Life Assessmentmentioning
confidence: 99%